A cyclonic gyre in an ice‐covered lake. (15th January 2013) - Forrest, Alexander L.; Laval, Bernard E.; Pieters, Roger; S. S. Lim, Darlene
Abstract : Observations of a cyclonic gyre in an ice‐covered, midsize (< 5 km 2 ), temperate lake are presented. Horizontal and vertical measurements of temperature and electrical conductivity measurements were collected using a conductivity‐temperature‐depth logger mounted on an autonomous underwater vehicle and additional instrumentation. These measurements revealed a cylindrical density anomaly with a radius of ∼110 m extending from the surface to ∼14 m depth. The observed radius is smaller than the internal Rossby radius of deformation (∼ 200 m), which suggests a cyclogeostrophic balance between centripetal, Coriolis, and pressure forces. The maximum azimuthal velocity, calculated assuming this balance, was ∼ 2.1 cm s −1 at 6–8 m depth. The Rossby number associated with this velocity was 1.7; this is consistent with the cyclogeostrophic assumption (i.e., Rossby number > 1) and nearly twice that of similar under‐ice eddies in the Arctic Ocean. The estimated Ekman spin‐down timescale is 1.5–15 d, but despite this, the gyre appeared to be relatively unchanged over 6 d of field observations. This persistence implies the gyre was forced over the course of the field study; however, the source of the forcing is unknown. Horizontal temperature transects at and below the bottom of the gyre revealed coherent temperature fluctuations suggestive of vertical transport associated with the gyre.